A high refractive index microlens array light extraction layer with circular polarization selectivity and a preparation method and application thereof

CN122984102APending Publication Date: 2026-10-27NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611114753.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]针对现有技术中微透镜阵列填充因子低、材料折射率较低、无机材料柔性差且缺乏圆偏振选择性等缺陷,本发明提供一种具有圆偏振选择性的高折射率微透镜阵列光提取层及其制备方法和应用,本发明通过分子设计将高摩尔极化率的硫原子、芳香环及手性单元引入聚合物主链,结合优化的光刻热回流工艺,实现高折射率材料与高密度微透镜结构的协同光提取,并赋予器件高发光效率和圆偏振光选择性透过/反射特性

Benefits of technology

[0045](1)本发明利用含硫芳香族聚合物的高摩尔极化率特性(硫原子摩尔折射度7.69cm³/mol,苯环25.46 cm³/mol),结合手性单元的手性光学活性,构建了一类兼具高折射率、圆偏振选择性和优异加工性能的光提取层,实现了平均折射率1.65-1.85与高透明度(>92%)的统一,有效匹配OLED发光层折射率,减少界面反射;通过光刻热回流的工艺,在保持微透镜光学形貌的前提下,将填充因子从传统热回流法的约60%提升至80%以上,显著增加有效出光面积。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122984102A_ABST
    Figure CN122984102A_ABST
Patent Text Reader

Abstract

The application provides a high-refractive microlens array light extraction layer with circular polarization selectivity and a preparation method and application thereof, and belongs to the technical field of organic photoelectric materials and micro-nano optical devices. The light extraction layer comprises a substrate and a microlens array composed of a plurality of microlens units on the substrate; and the microlens units are prepared from a chiral high-refractive sulfur-containing aromatic polymer. Through material design and structure regulation, the prepared light extraction layer realizes a high transparency of >92% in the range of an average refractive index of 1.65-1.85, effectively matches the refractive index of an OLED light-emitting layer and an interface layer, and significantly inhibits interface reflection loss; through a photolithography hot reflow process, the filling factor is improved from about 60% of a traditional hot reflow method to more than 80% under the premise of maintaining good optical morphology of the microlens, and the light extraction efficiency and the circular polarization light asymmetry factor of the device are comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic optoelectronic materials and micro / nano optical devices, specifically relating to a high-refractive-index microlens array light extraction layer with circular polarization selectivity, its preparation method, and its application. Background Technology

[0002] Organic light-emitting diodes (OLEDs) have become the mainstream of next-generation display and lighting technologies due to their advantages such as self-emission, wide viewing angle, and flexibility. However, due to the large refractive index mismatch between the organic light-emitting layer and air (organic layer n≈1.7-1.8, air n=1.0), according to Snell's law, total internal reflection occurs when the incident angle is greater than the critical angle. This results in approximately 70%-80% of photons being trapped inside the device (waveguide modes, substrate modes, and surface plasmon polariton modes), leading to an actual external quantum efficiency (EQE) far lower than the theoretical value. Therefore, light extraction technology has become crucial for overcoming the efficiency bottleneck of OLEDs.

[0003] Existing light extraction technologies are mainly divided into two categories: structural and material-based. Structural technologies, such as microlens arrays (MLAs), disrupt total internal reflection by altering the optical path angle. However, MLAs prepared using traditional photoresist thermal reflow methods typically have a fill factor below 70%, resulting in significant light energy loss. Furthermore, conventional photoresists (such as SU-8 and AZ series) have low refractive indices (n < 1.6), which differ greatly from the refractive index of the OLED emissive layer, leading to severe interface reflection. They also lack selective control over circularly polarized light (CPL), failing to meet the application requirements of 3D displays, anti-counterfeiting encryption, and glare reduction. Material-based technologies use high-refractive-index (n > 1.7) materials as the light extraction layer. However, inorganic materials (such as TiO2 and ZnS) are brittle and require high processing temperatures, making them unsuitable for flexible devices. Organic-inorganic hybrid materials face scattering losses and increased haze due to nanoparticle aggregation. Typically, electroluminescent devices achieve polarized light output by integrating external polarizers, but external polarizers are limited by the theoretical limit of 50% polarization polarizability. To date, an irreconcilable contradiction remains: the polarizability and luminous efficiency of polarized electroluminescent devices cannot be simultaneously optimized. For example, high polarizability polarized electroluminescent devices often have low luminous efficiency, while high luminous efficiency polarized electroluminescent devices have unsatisfactory polarizability.

[0004] Therefore, developing all-organic polymer microlens arrays with high refractive index (n>1.65), high transparency (T>90%), high luminous efficiency, excellent film-forming properties, and circular polarization polarizability is of great significance for realizing efficient, flexible, and large-area light extraction 3D displays and intelligent interactive displays. Summary of the Invention

[0005] To address the shortcomings of existing technologies, such as low fill factor of microlens arrays, low refractive index of materials, poor flexibility of inorganic materials, and lack of circular polarization selectivity, this invention provides a high refractive index microlens array light extraction layer with circular polarization selectivity, its preparation method, and its application. This invention introduces sulfur atoms, aromatic rings, and chiral units with high molar polarizability into the polymer backbone through molecular design, combined with an optimized photolithography and thermal reflow process, to achieve synergistic light extraction of high refractive index materials and high-density microlens structures, and endows the device with high luminous efficiency and circular polarization selective transmission / reflection characteristics.

[0006] Technical solution:

[0007] (i) A light extraction layer of a high refractive index microlens array with circular polarization selectivity, comprising a substrate and a microlens array composed of a plurality of microlens units located on the substrate; wherein the microlens units have circular polarization selectivity and light extraction characteristics, and are composed of a chiral high refractive index sulfur-containing aromatic polymer;

[0008] The general structural formula of the sulfur-containing aromatic polymer is as follows:

[0009]

[0010] Wherein, n is the degree of polymerization, taking the value of an integer from 1000 to 5000; Ar1 ​​is a unit containing a fused-ring aromatic hydrocarbon or a sulfur / oxygen / carbonyl-bridged aromatic ring, wherein Ar1 is selected from the following structures:

[0011] ;

[0012] The Ar2 has a chiral unit, and the Ar2 is selected from the following structures:

[0013]

[0014] * indicates a connection point.

[0015] Preferably, the sulfur-containing aromatic polymer is selected from one of the following compounds:

[0016] .

[0017] Preferably, the diameter of the microlens unit is 5-50 μm and the sagittal height is 2-50 μm.

[0018] Preferably, the microlens array is arranged in a hexagonal close-packed, circular, or square array.

[0019] (ii) The present invention provides a method for preparing a light extraction layer of a high refractive index microlens array with circular polarization selectivity.

[0020] S1. Dissolve raw material A containing Ar1, raw material B containing Ar2, and photoinitiator in an organic solvent to obtain a photoresist solution;

[0021] S2. The photoresist solution is coated onto the substrate surface using a spin coating process. By controlling the rotation speed and coating time, a liquid film of the target thickness is obtained. Subsequently, the substrate is placed on a hot plate for pre-baking treatment to obtain a prepolymer film. The pre-baking treatment is used to remove residual solvent and densify the film.

[0022] S3. A contact UV lithography system is used to selectively expose the prepolymer film through a chromium mask with a specific through-hole array pattern. In the exposed area, raw material A and raw material B undergo a photocrosslinking reaction under UV irradiation to form an insoluble network, while the unexposed area remains soluble, achieving precise pattern transfer. During exposure, raw material A and raw material B undergo a photocrosslinking reaction (specifically, UV-cured polymerization) to generate a sulfur-containing aromatic polymer with a main chain containing sulfide bonds (-S-) and aromatic ring structures. The photocrosslinking reaction formula is as follows:

[0023] ;

[0024] S4. Place the exposed substrate on a hot stage for hardening treatment. After the substrate cools to room temperature, immerse it in the developer for development. Then, fix, rinse with deionized water and dry with nitrogen to obtain the micropillar array.

[0025] Hardening treatment is used to promote the complete crosslinking reaction and release the internal stress generated during exposure. After the substrate cools to room temperature, it is immersed in the developer for development, selectively dissolving and removing the unexposed uncrosslinked areas. Then, it is fixed with isopropanol, rinsed with deionized water and dried with nitrogen to obtain a micropillar array with precise geometric dimensions.

[0026] S5. Using a stepped hot reflux process, the substrate with the micropillar array is transferred to a hot stage or tubular furnace cavity that has been preheated to the target reflux temperature and held for a period of time. The micropillar array melts and shrinks into a spherical microlens unit, which is then cooled in the furnace or naturally cooled to room temperature to solidify, thus obtaining the microlens array light extraction layer.

[0027] In step S5, the target reflux temperature for the stepped reflux is 80–160℃, and the temperature is maintained at the target temperature for 30–50 minutes. Under the action of the target reflux temperature of 80–160℃, driven by surface tension, the solid micropillars melt and spontaneously shrink to transform into a spherical crown-shaped structure with minimum surface energy. After maintaining the temperature at the target temperature for 30–50 minutes to ensure morphological stability, the structure is cooled in the furnace or naturally cooled to room temperature for shaping, ultimately obtaining a structure with a high filler factor (>80%) and low surface roughness (R0). a A light extraction layer of a microlens array (<1nm).

[0028] Preferably, in S1:

[0029] (1) The initiator is one of 1-hydroxycyclohexylphenyl ketone (UV-184), 2-methyl-1-(4-methylthiophenyl)-2-morpholin-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinphenyl)butanone, benzophenone, isopropylthioxanthone, and 4-methylbenzophenone;

[0030] (2) The organic solvent is one of tetrahydrofuran, propylene glycol methyl ether, dichloromethane, toluene or N,N-dimethylformamide.

[0031] Preferably, in S2:

[0032] (1) The substrate is one of the following: glass substrate, silicon wafer substrate, polyethylene terephthalate (PET) flexible substrate, and polyethylene naphthalate (PEN) substrate that has been plasma cleaned or hydrophilically treated;

[0033] (2) When using the spin coating process to obtain a liquid film, the spin coating program is set to an initial speed of 500 rpm / s, and the solution is added dropwise for 10 seconds. Then, the speed is accelerated to the target speed of 1500-2500 rpm / s at an acceleration of 500-2000 rpm / s, and maintained for 30-60 seconds to obtain a uniform liquid film.

[0034] (3) The pre-baking temperature is 60℃-95℃ and the baking time is 10-15 minutes.

[0035] Preferably, in S3:

[0036] (1) Specific array pattern: the through holes are circular, square or hexagonal, and the array is a circular, square or hexagonal array;

[0037] (2) Selective exposure conditions for the prepolymer film: 365 nm ultraviolet light exposure, light intensity 10 mW / cm², exposure time 20-100 seconds.

[0038] Preferably, in S4:

[0039] (1) The conditions for hardening the film are: baking for 5–10 minutes at a temperature of 70-100℃, which is higher than the pre-baking temperature.

[0040] (2) The developer is one of the following: a mixture of 1,2-dichlorobenzene and ethanol, propylene glycol methyl ether acetate (PGMEA), cyclopentanone, and chloroform;

[0041] (3) The fixing solution is ethanol or isopropanol;

[0042] (4) The developing time is 40-55 seconds and the fixing time is 10-20 seconds.

[0043] (iii) Application of the above-mentioned high refractive index microlens array light extraction layer with circular polarization selectivity in organic light-emitting diodes (OLEDs), quantum dot light-emitting diodes (QLEDs), solar cells or complementary metal-oxide-semiconductor (CMOS) image sensors.

[0044] Beneficial effects:

[0045] (1) This invention utilizes the high molar polarizability of sulfur-containing aromatic polymers (molar refractive index of sulfur atoms 7.69 cm³ / mol, benzene ring 25.46 cm³ / mol) and combines the chiral optical activity of chiral units to construct a type of light extraction layer that has high refractive index, circular polarization selectivity and excellent processing performance. It achieves the unity of average refractive index of 1.65-1.85 and high transparency (>92%), effectively matching the refractive index of OLED light-emitting layer and reducing interface reflection. Through the photolithography hot reflow process, while maintaining the optical morphology of microlenses, the fill factor is increased from about 60% in the traditional hot reflow method to more than 80%, which significantly increases the effective light-emitting area.

[0046] (2) The sulfur-containing aromatic polymer can be prepared by UV curing, and the process is compatible with flexible substrates (PET, PEN) and is suitable for roll-to-roll (R2R) production. When applied to OLED devices, the current efficiency can be improved by more than 30% through the dual mechanism of refractive index matching and microlens angle control, without affecting the electrical performance of the device.

[0047] (3) The light extraction layer of the microlens array prepared by the present invention has selective transmittance differences for left-handed and right-handed circularly polarized light. The transmittance difference ΔT between right-handed circularly polarized light (R-CPL) and left-handed circularly polarized light (L-CPL) of the microlens array is >5%.

[0048] (4) The surface roughness R of the light extraction layer of the microlens array prepared in this invention a <1 nm. Attached Figure Description

[0049] Figure 1 This is a schematic diagram of the structure of the high refractive index microlens array light extraction layer with circular polarization selectivity of the present invention;

[0050] Figure 2 This is a schematic diagram of the fabrication process of the high refractive index microlens array light extraction layer with circular polarization selectivity of the present invention;

[0051] Figure 3 This is a refractive index diagram of the light extraction layer P1 of the microlens array in Embodiment 1 of the present invention;

[0052] Figure 4This is a microscopic image of the light extraction layer P1 of the microlens array in Embodiment 1 of the present invention.

[0053] Figure 5 This is a scanning electron microscope (SEM) image of the light extraction layer P1 of the microlens array in Embodiment 1 of the present invention;

[0054] Figure 6 The diagram shows the asymmetry factor of the circularly polarized light emitted by the OLED induced by the light extraction layer P1 of the microlens array in Embodiment 1 of the present invention. The device structure is P1 / GLASS / ITO / PEDOT:PSS / Super Yellow / TPBi / LiF / Al.

[0055] Figure 7 This is a refractive index diagram of the light extraction layer P2 of the microlens array in Embodiment 2 of the present invention;

[0056] Figure 8 This is a microscopic image of the light extraction layer P2 of the microlens array in Embodiment 2 of the present invention.

[0057] Figure 9 This is a scanning electron microscope (SEM) image of the light extraction layer P2 of the microlens array in Embodiment 2 of the present invention;

[0058] Figure 10 The diagram shows the asymmetry factor of the circularly polarized light emitted by the OLED induced by the light extraction layer P2 of the microlens array in Embodiment 2 of the present invention. The device structure is P2 / GLASS / ITO / PEDOT:PSS / Super Yellow / TPBi / LiF / Al.

[0059] Figure 11 This is a refractive index diagram of the light extraction layer P3 of the microlens array in Embodiment 3 of the present invention;

[0060] Figure 12 This is a microscopic image of the light extraction layer P3 of the microlens array in Embodiment 3 of the present invention.

[0061] Figure 13 This is a scanning electron microscope (SEM) image of the light extraction layer P3 of the microlens array in Embodiment 3 of the present invention;

[0062] Figure 14 The diagram shows the asymmetry factor of the circularly polarized light emitted by the OLED induced by the light extraction layer P3 of the microlens array in Embodiment 3 of the present invention. The device structure is P3 / GLASS / ITO / PEDOT:PSS / Super Yellow / TPBi / LiF / Al. Detailed Implementation

[0063] The technical solution of the present invention will be described in detail below through embodiments, but the scope of protection of the present invention is not limited to the embodiments described. Unless otherwise specified, the experimental methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and materials can be obtained commercially.

[0064] The schematic diagram of the high-refractive-index microlens array light extraction layer with circular polarization selectivity of the present invention is shown below. Figure 1 As shown, a schematic diagram of the fabrication process of the high-refractive-index microlens array light extraction layer with circular polarization selectivity of the present invention is as follows. Figure 2 As shown.

[0065] Example 1

[0066] Select Ar1 as Ar2 is The specific preparation steps of the microlens array light extraction layer P1 are as follows:

[0067] S1. Two raw materials containing Ar1 (0.1 mmol, 1 equiv.) and Ar2 (0.1 mmol, 1 equiv.) are dissolved in toluene along with the photoinitiator 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone (0.004 mmol, 0.04 equiv.). After stirring, a photoresist solution R1 with a concentration of 10 mg / mL (the total concentration of the two raw materials and the photoinitiator is 10 mg / mL) is prepared.

[0068] S2. Using a spin-coating process, the prepared photoresist solution R1 is spin-coated onto the surface of a hydrophilically treated glass substrate to form a uniform liquid film with a thickness of approximately 5 μm. Subsequently, the substrate is placed on a hot plate for pre-baking at 80°C for 10 minutes to remove residual solvent and densify the film, thereby obtaining a prepolymer film.

[0069] S3. Employs a contact ultraviolet lithography system (wavelength 365 nm, light intensity 10 mW / cm²). 2 The film was exposed using a chrome mask (a square array of circular through-holes with a diameter of 15 μm) at an exposure dose of 300 mJ / cm². 2 (Corresponding to an exposure time of 30 seconds). The photoresist within the exposed area undergoes a photocrosslinking reaction, as shown in the following equation:

[0070]

[0071] S4. After exposure, the substrate is placed on a hot plate for hardening treatment and baked at 85°C for 5 minutes to promote the complete crosslinking reaction and release residual stress. After the substrate cools to room temperature, it is immersed in the developer (propylene glycol methyl ether acetate, PGMEA) for 40 seconds to dissolve and remove unexposed, uncrosslinked areas. Then, it is fixed with isopropanol for 10 seconds and dried with nitrogen to form a square array P1 composed of cylindrical micropillars with a diameter of 15 μm and a height of 15 μm, with a spacing of 10 μm between the edges of adjacent micropillars.

[0072] The basic operating procedure of S5 step-by-step reflow is as follows: First, the substrate with the micropillar array is placed horizontally in the cavity of the temperature-controlled reflow equipment, and atmospheric pressure air, vacuum or inert gas atmosphere is selected for protection according to the material characteristics; then, the step-by-step temperature program is started, starting from room temperature, and the temperature is increased in increments of 5℃ (e.g., room temperature → 30℃ → 35℃ → 40℃... until the selected target reflow temperature), and the heating rate is set at 1–3℃ / min between adjacent steps; when the temperature gradually rises to the specific target value in the range of 80-160℃, the step-by-step heating is stopped and the main reflow stage is entered. The temperature is held constant at the target temperature for 30–50 minutes to allow the solid micropillars to fully melt and spontaneously shrink under the drive of surface tension to transform into a microlens structure with minimum surface energy.

[0073] In this embodiment, the substrate with the micropillar array is placed directly on a hot stage preheated to a target temperature of 160°C for stepped thermal reflux, and held at this temperature for 30 minutes under a nitrogen atmosphere. Under the action of surface tension, the cylindrical micropillars melt and shrink into spherical microlens units, which are then cooled to room temperature in the furnace to solidify, resulting in the microlens array light extraction layer P1 (containing the glass substrate).

[0074] The relevant test results are as follows: Atomic force microscopy (AFM) analysis showed that the diameter of the microlens unit is approximately 18 μm, and the sagitta is approximately 3 μm. The arithmetic mean roughness R of the light extraction layer P1 of the microlens array is... a The light extraction layer P1 of the microlens array has a wavelength of 0.65 nm. Image analysis software calculated the fill factor to be 82%. UV-Vis-NIR spectrophotometry showed that the visible light transmittance of the light extraction layer P1 was 96%. Ellipsometry analysis revealed that the average refractive index of the light extraction layer P1 (with the refractive index at 550 nm as the average) was 1.85. Magnetic circular polarization spectrometry determined the circular polarization selectivity of the light extraction layer P1. Comparison of OLED devices with and without the light extraction layer showed a 37% increase in luminous efficiency. Figure 3 Characterization of the refractive index of the light extraction layer P1 of the microlens array. Figure 4 This is a microscopic image of the structure of the light extraction layer P1 of the microlens array. Figure 5 This is a scanning electron microscope (SEM) image of the light extraction layer P1 of the microlens array. Figure 6 The diagram shows the asymmetry factor of the circularly polarized light emitted by the OLED induced by the light extraction layer P1 of the microlens array obtained in Example 1 of this invention. The asymmetry factor glum reflects the selectivity of the chiral compound for left- or right-handed circularly polarized light during the light emission process. The device structure is P1 / GLASS / ITO / PEDOT:PSS / Super Yellow / TPBi / LiF / Al.

[0075] The above characterization results collectively demonstrate that the microlens arrays prepared by photolithography-thermal reflow process possess the characteristics of high refractive index, high fill factor, and low surface roughness, which can significantly reduce interfacial total internal reflection loss and are suitable for high-efficiency light extraction devices.

[0076] Example 2

[0077] Select Ar1 as Ar2 is The fabrication steps of the microlens array light extraction layer P2 are as follows:

[0078] S1. Two raw materials containing Ar1 (1.244 mmol, 1 equiv.) and Ar2 (1.244 mmol, 1 equiv.) and the photoinitiator isopropylthioxanthone (0.004 mmol, 0.04 equiv.) are dissolved in dichloromethane and stirred to prepare a photoresist solution R2 with a concentration of 8 mg / mL.

[0079] S2. Using a spin coating method, photoresist solution R2 is spin-coated onto a hydrophilic glass substrate to obtain a 4 μm thick film, which is then pre-baked at 70°C for 12 minutes.

[0080] S3, Employs a 365 nm ultraviolet lithography machine (light intensity 10 mW / cm²). 2 Exposure was performed through a chrome mask (a square array of circular through-holes with a diameter of 12 μm) at an exposure dose of 250 mJ / cm². 2 (Corresponding exposure time 25 seconds). The photoresist within the exposed area undergoes a photocrosslinking reaction, as shown in the following equation:

[0081]

[0082] S4. After exposure, place the substrate on a hot plate for hardening treatment at 75°C for 6 minutes. After the substrate cools to room temperature, develop it with chloroform for 40 seconds, fix it with isopropanol for 10 seconds, rinse with deionized water, and dry it with nitrogen to form a square array P2 composed of cylindrical micropillars with a diameter of 12 μm and a height of 4 μm, with a spacing of 4 μm between the edges of adjacent micropillars.

[0083] S5. Place the micropillar array P2 directly on a preheated hot stage at 150°C in air for hot reflow. Maintain the temperature for 35 minutes to transform the cylindrical micropillars into spherical microlens units. Cool the microlens to room temperature with the furnace to set the shape and obtain the microlens array light extraction layer P2.

[0084] Atomic force microscopy (AFM) analysis revealed that the microlens unit has a diameter of approximately 12 μm and a height of approximately 2.5 μm. AFM also showed that the arithmetic mean roughness R of the light extraction layer surface is... a The light extraction layer of this microlens array has a wavelength of 0.58 nm; its fill factor is 80%; the transmittance in the visible region is 93% as measured by a UV-Vis-NIR spectrophotometer; the average refractive index is 1.77 as measured by an ellipsometer; and its circular polarization selectivity is measured by a magnetic circular polarization spectrometer. A comparison between OLED devices containing and without the light extraction layer shows that the luminous efficiency of the light extraction layer reaches 30%. Figure 7 Characterization of the refractive index of the light extraction layer P2 of the microlens array. Figure 8 This is a microscopic image of the P2 microlens array light extraction layer. Figure 9 This is a scanning electron microscope (SEM) image of the light extraction layer P2 of the microlens array. Figure 10 The diagram shows the asymmetry factor of the circularly polarized light emitted by the OLED induced by the P2 light extraction layer of the microlens array obtained in Example 2 of this invention. The asymmetry factor glum reflects the selectivity of chiral compounds for left- or right-handed circularly polarized light during the luminescence process. The device structure is P2 / GLASS / ITO / PEDOT:PSS / Super Yellow / TPBi / LiF / Al.

[0085] Example 3

[0086] Select Ar1 as Ar2 is The fabrication steps of the microlens array light extraction layer P3 are as follows:

[0087] S1. Two raw materials containing Ar1 (1.244 mmol, 1 equiv.) and Ar2 (1.244 mmol, 1 equiv.) are dissolved in tetrahydrofuran along with the photoinitiator 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone (0.004 mmol, 0.04 equiv.). After stirring, a photoresist solution R3 with a concentration of 8 mg / mL is prepared.

[0088] S2. Using the spin coating method, the photoresist solution R3 is spin-coated onto a flexible polyethylene terephthalate (PET) substrate to obtain a 6 μm thick film. Then, it is pre-baked on a hot plate at a temperature of 60°C for 15 minutes.

[0089] S3, Employs a 365 nm ultraviolet lithography machine (light intensity 10 mW / cm²). 2 Exposure was performed using a chrome mask (a square array of circular through-holes with an outer diameter of 20 μm) at an exposure dose of 400 mJ / cm². 2 (Corresponding exposure time 40 seconds). The photoresist in the exposed area undergoes a photocrosslinking reaction, as shown in the following equation:

[0090]

[0091] S4. Subsequently, a hardening process was performed, and the film was baked at 70°C for 8 minutes. The film was developed with a developer (cyclopentanone and isopropanol volume ratio 1:1) for 50 seconds, fixed with isopropanol for 10 seconds, rinsed with deionized water, and dried with nitrogen to form a square array of cylindrical micropillars with a diameter of 20 μm and a height of 6 μm, with a spacing of 2 μm between the edges of adjacent micropillars.

[0092] S5. The sample is placed directly on a hot stage preheated to 140°C under nitrogen protection for hot reflux. After being kept at the same temperature for 40 minutes, the cylindrical micropillars melt and shrink into spherical microlens units. The microlens units are then cooled to room temperature in the furnace to solidify, resulting in the microlens array light extraction layer P3.

[0093] Atomic force microscopy (AFM) analysis revealed that the diameter of the spherical microlens unit is approximately 20 μm, and its sagitta is approximately 4 μm. AFM also showed that the arithmetic mean roughness R of the light extraction layer P3 of the microlens array surface is... a The wavelength is 0.82 nm; the P3 fill factor of the light extraction layer of this microlens array is 90%; the transmittance in the visible region is 94% as measured by UV-Vis-NIR spectrophotometry; the average refractive index is 1.76 as measured by ellipsometer; and its circular polarization selectivity is measured by magnetic circular polarization spectrometry. A comparison between OLED devices containing the light extraction layer and those without shows that the luminous efficiency is increased by 28%.

[0094] Figure 11 Characterization of the refractive index of the light extraction layer P3 of the microlens array. Figure 12 This is a microscopic image of the P3 microlens array light extraction layer. Figure 13 This is a scanning electron microscope (SEM) image of the microlens array P3. Figure 14 The diagram shows the asymmetry factor of the circularly polarized light emitted by the OLED induced by the P3 light extraction layer of the microlens array obtained in Example 3 of the present invention. The asymmetry factor glum reflects the selectivity of the chiral compound for left- or right-handed circularly polarized light during the light emission process. The device structure is P3 / GLASS / ITO / PEDOT:PSS / Super Yellow / TPBi / LiF / Al.

[0095] Example 4

[0096] Select Ar1 as Ar2 is Fabrication of the light extraction layer P4 of the microlens array:

[0097] S1. Dissolve the two raw materials containing Ar1 (1.244 mmol, 1 equiv.) and Ar2 (1.244 mmol, 1 equiv.) and the photoinitiator benzophenone (0.004 mmol, 0.04 equiv.) in tetrahydrofuran, and after stirring, prepare a photoresist solution R4 with a concentration of 15 mg / mL.

[0098] S2. Using a spin coating method, photoresist solution R4 is spin-coated onto a polyethylene naphthalate (PEN) substrate to obtain an 8 μm thick film, which is then pre-baked at 90°C for 8 minutes.

[0099] S3, Employs a 365 nm ultraviolet lithography machine (light intensity 10 mW / cm²). 2 Exposure was performed through a chrome mask (a square array of circular through-holes with a diameter of 25 μm) at an exposure dose of 500 mJ / cm². 2 (Corresponding to an exposure time of 50 seconds). The photoresist within the exposed area undergoes a photocrosslinking reaction, as shown in the following equation:

[0100]

[0101] S4. Hardening treatment was performed at 95°C for 10 minutes. Development was carried out for 60 seconds using a mixture of N,N-dimethylformamide and isopropanol (volume ratio 3:1), followed by rinsing with isopropanol and drying with nitrogen to form a square array of cylindrical micropillars with a diameter of 25 μm and a height of 8 μm, with a spacing of 5 μm between the edges of adjacent micropillars.

[0102] S5. The sample is placed directly on a hot stage preheated to 130°C under a nitrogen atmosphere for hot reflux for 50 minutes to form a spherical microlens unit. The sample is then cooled to room temperature in the furnace to set the shape, resulting in the microlens array light extraction layer P4.

[0103] The microlens unit has a diameter of approximately 25 μm and a height of approximately 5 μm. Atomic force microscopy (AFM) analysis shows that the arithmetic mean surface roughness R of the light extraction layer P4 of the microlens array is... a The light extraction layer of this microlens array has a wavelength of 0.95 nm; the P4 fill factor is 82%; the transmittance in the visible region is 92% as measured by a UV-Vis-NIR spectrophotometer; the average refractive index is 1.72 as measured by an ellipsometer; and its circular polarization selectivity is measured by a magnetic circular polarization spectrometer. A comparison between OLED devices with and without the light extraction layer shows that the luminous efficiency is increased by 30%.

[0104] Example 5

[0105] Select Ar1 as Ar2 is Fabrication of the light extraction layer P5 of the microlens array:

[0106] S1. Dissolve the two raw materials containing Ar1 (0.1 mmol, 1 equiv.) and Ar2 (0.1 mmol, 1 equiv.) and isopropylthioxanthone photoinitiator (0.004 mmol, 0.04 equiv.) in N,N-dimethylformamide, stir for 10 minutes, and prepare a photoresist solution R5 with a concentration of 10 mg / mL.

[0107] S2. Using a spin coating process, photoresist solution R5 is spin-coated onto the surface of a plasma-cleaned silicon substrate to form a uniform liquid film with a thickness of approximately 5 μm. The substrate is then placed on a hot plate for pre-baking at 65°C for 12 minutes to remove residual solvent and densify the photoresist film.

[0108] S3. Employs a contact ultraviolet lithography system (wavelength 365 nm, light intensity 10 mW / cm²). 2 The film was exposed using a chrome mask (a square array of circular through-holes with a diameter of 18 μm) at an exposure dose of 350 mJ / cm². 2 (Corresponding to an exposure time of 35 seconds), causing a photocrosslinking reaction in the photoresist within the exposed area. The photocrosslinking reaction in the exposed area is as follows:

[0109]

[0110] S4. After exposure, the substrate is placed on a hot plate for hardening treatment and baked at 75°C for 6 minutes to promote the complete crosslinking reaction and release residual stress. After the substrate cools to room temperature, it is immersed in developer (PGMEA) for development for 45 seconds to dissolve and remove unexposed, uncrosslinked areas. Then, it is fixed with isopropanol for 15 seconds, rinsed with deionized water, and dried with nitrogen to form a square array of cylindrical micropillars with a diameter of 18 μm and a height of 5 μm, with a spacing of 2.5 μm between the edges of adjacent micropillars.

[0111] S5. The sample is placed directly on a hot stage preheated to 145°C under a nitrogen atmosphere for hot reflux. The temperature is maintained for 35 minutes, and then cooled to room temperature with the furnace for shaping. Under the action of surface tension, the cylindrical micropillars melt and shrink into spherical microlens units, forming the microlens array light extraction layer P5.

[0112] Atomic force microscopy (AFM) analysis showed that the arithmetic mean surface roughness of the light extraction layer P5 in the microlens array was 0.75 nm. Image analysis software determined that the fill factor of the light extraction layer P5 was 83%. UV-Vis-NIR spectrophotometry showed an average transmittance of 97% in the visible light region. Ellipsometry analysis revealed an average refractive index of 1.79. Magnetic circular polarization spectroscopy (MBPS) confirmed its circular polarization selectivity. A comparison of OLED devices containing the light extraction layer with those without showed a 27% increase in luminous efficiency.

[0113] Example 6

[0114] Select Ar1 as Ar2 is Fabrication of the light extraction layer P6 of the microlens array:

[0115] S1. Dissolve the two raw materials containing Ar1 (0.1 mmol, 1 equiv.) and Ar2 (0.1 mmol, 1 equiv.) and 4-methylbenzophenone photoinitiator (0.004 mmol, 0.04 equiv.) in propylene glycol methyl ether, stir for 10 minutes, and prepare a photoresist solution R6 with a concentration of 14 mg / mL.

[0116] S2. Using a spin-coating process, photoresist solution R6 is spin-coated onto the surface of a plasma-cleaned silicon wafer substrate to form a uniform liquid film with a thickness of approximately 7 μm. The substrate is then placed on a hot plate for pre-baking at 95°C for 8 minutes to thoroughly remove residual solvent.

[0117] S3. Employs a contact ultraviolet lithography system (wavelength 365 nm, light intensity 10 mW / cm²). 2The film was exposed using a chrome mask (a square array of circular through-holes with a diameter of 15 μm) at an exposure dose of 480 mJ / cm². 2 (Corresponding exposure time 48 seconds). The photoresist in the exposed area undergoes a photocrosslinking reaction, as shown in the following equation:

[0118]

[0119] S4. After exposure, the substrate is placed on a hot plate for hardening treatment and baked at 105°C for 9 minutes to enhance the adhesion between the film and the substrate. After the substrate cools to room temperature, it is immersed in a developer solution (1,2-dichlorobenzene and ethanol, volume ratio 1:3) for 55 seconds to dissolve unexposed areas. Then, it is fixed with ethanol for 20 seconds, rinsed with deionized water, and dried with nitrogen to form a square array of cylindrical micropillars with a diameter of 15 μm and a height of 7 μm, with a spacing of 3.5 μm between the edges of adjacent micropillars.

[0120] S5. The sample was placed directly on a hot stage preheated to 130°C under a nitrogen atmosphere for hot reflux for 40 minutes. The cylindrical micropillars were transformed into spherical microlens units under the action of surface tension. The microlens array light extraction layer P6 was obtained by cooling to room temperature with the furnace.

[0121] Atomic force microscopy measurements showed that the microlens unit diameter was approximately 15 μm and the sagitta was approximately 4.5 μm. The arithmetic mean roughness R of the light extraction layer P6 of the microlens array was [not specified]. a The light extraction layer of this microlens array has a wavelength of 0.68 nm; the P6 fill factor is 80%; the average transmittance in the visible region is 94% as measured by UV-Vis-NIR spectrophotometry; the average refractive index is 1.78 as measured by ellipsometer; and its circular polarization selectivity is measured by magnetic circular polarization spectrometry. A comparison between OLED devices containing the light extraction layer and those without shows a 33% increase in luminous efficiency.

[0122] Example 7

[0123] Select Ar1 as Ar2 is The fabrication steps of the microlens array light extraction layer P7 are as follows:

[0124] S1. Dissolve the two raw materials containing Ar1 (0.1 mmol, 1 equiv.) and Ar2 (0.1 mmol, 1 equiv.) and benzophenone photoinitiator (0.004 mmol, 0.04 equiv.) in N,N-dimethylformamide, stir for 10 minutes, and prepare a photoresist solution R7 with a concentration of 13 mg / mL.

[0125] S2. Using a spin coating process, photoresist solution R7 is spin-coated onto the surface of a plasma-cleaned silicon wafer substrate to form a uniform liquid film with a thickness of approximately 6 μm. The substrate is then placed on a hot plate for pre-baking at 85°C for 11 minutes to remove residual solvent.

[0126] S3. Employs a contact ultraviolet lithography system (wavelength 365 nm, light intensity 10 mW / cm²). 2 The film was exposed using a patterned chrome mask (a square array of hexagonal through-holes with an outer diameter of 22 μm) at an exposure dose of 420 mJ / cm². 2 (Corresponding exposure time 42 seconds). The photoresist within the exposed area undergoes a photocrosslinking reaction, as shown in the following equation:

[0127]

[0128] S4. After exposure, place the substrate on a hot plate for hardening treatment and bake at 95°C for 7 minutes. After the substrate cools to room temperature, immerse it in a developer (N,N-dimethylformamide to isopropanol volume ratio 1:4) for development for 48 seconds. Then fix with isopropanol for 12 seconds, rinse with deionized water, and dry with nitrogen to form a square array of hexagonal micropillars with a diameter of 22 μm and a height of 6 μm, with a spacing of 3 μm between the edges of adjacent micropillars.

[0129] S5. The sample is placed directly on a hot stage preheated to 150°C under a nitrogen atmosphere for hot reflux. After 40 minutes of constant temperature, the hexagonal micropillars melt and shrink into spherical microlens units. The units are then cooled in the furnace (or naturally cooled) to room temperature to set, resulting in the microlens array light extraction layer P7.

[0130] Atomic force microscopy measurements showed that the microlens unit diameter was approximately 22 μm and the sagitta was approximately 3.8 μm. The arithmetic mean roughness R of the light extraction layer P7 of the microlens array was [not specified]. a The light extraction layer of this microlens array has a wavelength of 0.71 nm; the P7 fill factor is 81%; the average transmittance in the visible region is 94% as measured by UV-Vis-NIR spectrophotometry; the average refractive index is 1.8 as measured by ellipsometer; and its circular polarization selectivity is measured by magnetic circular polarization spectrometry. A comparison between OLED devices with and without the light extraction layer shows that the luminous efficiency is improved by 32%.

[0131] This invention, through material design and structural control, prepares a light extraction layer with a transparency of >92% in the range of average refractive index of 1.65-1.85, effectively matching the refractive index of the OLED light-emitting layer and the interface layer, and significantly suppressing interface reflection loss. Through photolithography and thermal reflow process, while maintaining the good optical morphology of the microlens, the fill factor is increased from about 60% in the traditional thermal reflow method to more than 80%, thereby comprehensively improving the light extraction efficiency of the device.

[0132] As described above, although the invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the invention itself. Various changes in form and detail may be made without departing from the spirit and scope of the invention.

Claims

1. A high-refractive-index microlens array light extraction layer with circular polarization selectivity, characterized in that, The device includes a substrate and a microlens array consisting of several microlens units located on the substrate; the microlens units are made of a chiral, high-refractive-index sulfur-containing aromatic polymer. The general structural formula of the sulfur-containing aromatic polymer is as follows: ; Wherein, n is the degree of polymerization, taking the value of an integer from 1000 to 5000; Ar1 ​​is a unit containing a fused-ring aromatic hydrocarbon or a sulfur / oxygen / carbonyl-bridged aromatic ring, wherein Ar1 is selected from the following structures: ; The Ar2 is selected from the following structures: ; * indicates a connection point.

2. The light extraction layer according to claim 1, characterized in that, The sulfur-containing aromatic polymer is selected from one of the following compounds: 。 3. The light extraction layer according to claim 1, characterized in that, The diameter of the microlens unit is 5-50 μm, and the sagittal height is 2-50 μm.

4. The light extraction layer according to claim 1, characterized in that, The microlens array is arranged in a hexagonal close-packed, circular, or square array.

5. The method for preparing the light extraction layer according to claim 1, characterized in that, Includes the following steps: S1. Dissolve raw material A containing Ar1, raw material B containing Ar2, and photoinitiator in an organic solvent to obtain a photoresist solution; S2. The photoresist solution is coated onto the substrate surface using a spin coating process to obtain a liquid film of the target thickness; then the substrate is placed on a hot plate for pre-baking treatment to obtain a prepolymer film. S3. A contact ultraviolet lithography system is used to selectively expose the prepolymer film through a chromium mask with a specific through-hole array pattern; raw material A and raw material B in the exposed area undergo a photocrosslinking reaction under ultraviolet light irradiation, and the photocrosslinking reaction formula is as follows: ; S4. Place the exposed substrate on a hot stage for hardening treatment. After the substrate cools to room temperature, immerse it in the developer for development. Then, fix, rinse with deionized water and dry with nitrogen to obtain the micropillar array. S5. Using a stepped hot reflux process, the substrate with the micropillar array is transferred to a hot stage or tubular furnace cavity that has been preheated to the target reflux temperature and held for a period of time. The micropillar array melts and shrinks into a spherical microlens unit, which is then cooled in the furnace or naturally cooled to room temperature to solidify, thus obtaining the microlens array light extraction layer.

6. The method for preparing the light extraction layer according to claim 5, characterized in that, In S1, the photoinitiator is one of 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, benzophenone, isopropylthioxanthone, and 4-methylbenzophenone; the organic solvent is one of tetrahydrofuran, propylene glycol methyl ether, dichloromethane, toluene, or N,N-dimethylformamide. In S2, the substrate is one of the following: a glass substrate that has been plasma cleaned or hydrophilically treated, a silicon wafer substrate, a flexible terephthalate substrate, or a polyethylene naphthalate substrate.

7. The method for preparing the light extraction layer according to claim 5, characterized in that, In S2, the pre-baking temperature is 60℃-95℃, and the baking time is 10–15 minutes; In S4, the hardening treatment conditions are: baking for 5–10 minutes at a temperature of 70–100℃, which is higher than the pre-baking temperature; In S5, the target reflux temperature is 80–160°C, and the temperature is maintained at the target temperature for 30–50 minutes.

8. The method for preparing the light extraction layer according to claim 5, characterized in that, In S3: (1) Specific array pattern: the through holes are circular, square or hexagonal, and the array is a circular, square or hexagonal array; (2) Selective exposure conditions for the prepolymer film: 365 nm ultraviolet light exposure, light intensity 10 mW / cm², exposure time 20-100 seconds.

9. The method for preparing the light extraction layer according to claim 5, characterized in that, In S4: (1) The developer is one of the following: a mixture of 1,2-dichlorobenzene and ethanol, propylene glycol methyl ether acetate, cyclopentanone, and chloroform; (2) The fixing solution is ethanol or isopropanol; (3) The developing time is 40-55 seconds and the fixing time is 10-20 seconds.

10. The application of the light extraction layer of claim 1 in organic light-emitting diodes, quantum dot light-emitting diodes, solar cells, or complementary metal-oxide-semiconductor image sensors.